Academic trip to Langkawi - Isnin, Nadrawina (UiTM Sarawak, 2016)
An academic trip funded by TAPA was organised for 32 Bachelor in Administrative Science (AM228) 5D students from 8th to 11th November, 2015. As the lecturer teaching this subject, I challenged this group to manage an actual project from the beginning till the end. This also means being involved in the organizational structure set up, work breakdown structure and other related features of project management such as the use of the Project Management software that must be monitored weekly. After much discussion, Langkawi was decided as their class project destination and the project was to be evaluated. A few programmes were planned for this trip, such as briefing with the Panorama Langkawi team, sightseeing in the SkyCab and SkyBridge, visiting MARDI Langkawi Agro Technology Park and Haji Ismail Group (HIG) Complex. The Project Leader, Kenneth Jarin was assisted by his team members and each group was headed by one leader.